Current topics in developmental biology. Volume 35 - Schatten, Gerald; ScienceDirect eBooks (San Diego, Calif. ; London : Academic Press, 1997)
Volume 35 proves to be essential reading for anyone interested in reactions between retinoid signaling pathways and the genes regulating cell proliferation/survival, developmentally-regulated changes in the nuclear envelope, the developmental roles of the EGFR, or ErbB family, the correspondence between phylogeny and life history in polyembryonic insect development, control of cadherin function by extracellular signals, the importance of the Spemann organizer for neural induction, and the study of signal transduction in Drosophila melanogaster.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Embryology; Cytogenetics; Chemical embryology; Clinical chemistry; SCIENCE -- Life Sciences -- Developmental Biology; Chemical embryology; Clinical chemistry; Cytogenetics; Embryology; Electronic books